Diálogos e (re)construções de um grupo de supervisores pedagógicos sobre as práticas formadoras: contribuições da pesquisa-formação - Lazarini, Kelly Cristina Teixeira (2022)
Teacher continuing professional development centered on the school has gained prominence in discussions and teacher training policies. The pedagogical supervisor is the professional responsible for developing and monitoring this training process. This professional favors the awareness of teachers by supporting and organizing the reflection on their pedagogical decisions and on the difficulties encountered in developing their work. Therefore, the supervisor assumes an important role in the professional development of their team. The supervisor also needs the training to play their function well because daily they are confronted by emergencies and needs, which they try to overcome. It often makes them leave aside their roles as pedagogical support to teachers and their professional growth. Given the above, the research on screen aimed to investigate the contributions of a research-training initiative to the rethinking of training practices in the context of a group of supervisors' schools. To this end, we have chosen qualitative approach research of the research-training type, with inspirations of action research. The research participants were 13 (thirteen) pedagogical supervisors of the municipal school network of a city in southern Minas Gerais. Questionnaires were applied and experience reports were heard in addition to participant observation, field diary elaboration, and training meetings with reflective records for data collection. The training topics were delineated based on the needs and priorities of the team in their work context, according to the observations of each meeting. The studies carried out allowed us to reaffirm the relevance of the pedagogical supervisor in the context of the school and as a teacher trainer. At the same time, they highlight the fragilities that involve this professional’s work in the school due to the overlapping of tasks and, often, the deviation from their functions due to the overflow of demands and challenges that arise daily and involve the school, the teachers, the students, the management and even the school community. Moreover, it made it possible to rethink and reframe the modes of professional performance and the training practices as supervisors and trainers in the context of basic education schools through research-training. Given the research results, a training was proposed as an Educational Product in the form of a course. It was developed in 10 meetings and entitled: “Pedagogical dialogues with school supervisors: possibilities of re-signification of training practices”.